The importance of emotions in the lives of children and young people in foster care in England, France and Germany. (17th January 2022) - Join‐Lambert, Hélène; Reimer, Daniela
Abstract: When foster care is discussed in research, emotions are mostly kept out of the scope. This article explores emotions narrated by young people in foster care and by their foster carers. It brings together findings from two studies: The first used biographical interviews conducted with 100 young people from Germany, while the second draws on ethnographic interviews with 12 young people from France and England. The analysis, in line with relevant literature, shows that although emotions are hardly mentioned directly, they seem to be highly relevant in understanding the experience of foster care. Therefore, we suggest, professionalism and emotions need to be understood as complementary elements.